Incorporating non‐academics in academic spin‐off entrepreneurial teams: the vertical diversity that can make the difference. (9th April 2021) - Ben‐Hafaïedh, Cyrine; Micozzi, Alessandra; Pattitoni, Pierpaolo
Abstract : To enhance the development of academic spin‐offs, surrogate (external) entrepreneurs are often added to the entrepreneurial team comprising academics. Existing research focused on entrepreneurial team diversity (horizontal member differences) and has mixed results. Vertical member differences (i.e., inequality) between academics and non‐academics are not addressed. However, strategic decision making is one of the main responsibilities of an entrepreneurial team. Decision‐making power, as reflected in ownership, in particular, is thus of the essence. Based on a sample of 164 Italian academic spin‐offs, this article investigates the impacts of both horizontal and vertical heterogeneity of entrepreneurial teams on the firms' performance. The findings confirm that surrogate entrepreneurs generally make a positive contribution to academic spin‐off performance but become counter‐productive when their presence overpowers that of academics.